Social algorithms of the Chinese company Huawei Technologies management model - N. Yu. Paudyal (Вестник университета)
The article deals with the problem of the conditionality of Huawei Technologies successful development by its social policy. Among the effective algorithms of the management model, the following are presented: the formation of a team of like-minded people from a conglomerate of thousands of employees of different nationalities using the principles of forced mobility, continuous education based on the company’s training centers, stratified material incentives and an official career elevator. The basis of the ideology of a stable society of workers is the teaching of Confucius, based on the formula: “Let the father be the father, the son be the son, the official be the official, and the sovereign be the sovereign” and the idea of a classless society in the theory of socialism. The concept of shared ownership, which was implemented by Huawei founder and President Ren Zhengfei, encourages team members to work intensively for the individual and common good. Social algorithms, which form the core of the management model, solve the global problem of ensuring the strength and stability, viability and longevity of a successful brand.